An Adaptive Finite Element PML Method for the Acoustic Scattering Problems in Layered Media (Communications in Computational Physics, 2018)
The paper concerns the numerical solution for the acoustic scattering problemsin a two-layer medium. The perfectly matched layer (PML) technique is adoptedto truncate the unbounded physical domain into a bounded computational domain.An a posteriori error estimate based adaptive finite element method is developed tosolve the scattering problem. Numerical experiments are included to demonstrate theefficiency of the proposed method.
Keywords: Acoustic scattering problems; layered media; perfectly matched layer; adaptive finite element method.